1997
DOI: 10.1557/jmr.1997.0395
|View full text |Cite
|
Sign up to set email alerts
|

Structure of grain boundaries: Correlation to supercurrent transport in textured Bi2Sr2Can−1CunOx bulk material

Abstract: Two kinds of characteristic grain boundaries were observed in textured Bi 2 Sr 2 Ca n21 Cu n O x (n 2 and 3) bulk material: one (P-type) is nearly parallel to the (001) plane, and the other (N-type) is approximately normal to the (001) plane. Low-angle tilt N-type boundaries are composed of arrays of dislocations. However, for a small c-axis misorientation, the regions between the dislocation cores are still well connected, providing "pathways" for supercurrents crossing the boundary plane. The P-type boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…the c-axis orientation of superconductor nuclei has no preferred direction with respect to the substrate (figure 6). In this fashion, and assuming anisotropic superconductor crystal growth behaviour where growth along the ab direction is preferred, as it has been shown in various investigations [12][13][14], one would predict that after a time interval t two rather different situations should develop from the nucleation event assumed in figure 6. It is assumed that during crystal growth the crystal shape develops into a plate-like configuration.…”
Section: Assumptionsmentioning
confidence: 76%
“…the c-axis orientation of superconductor nuclei has no preferred direction with respect to the substrate (figure 6). In this fashion, and assuming anisotropic superconductor crystal growth behaviour where growth along the ab direction is preferred, as it has been shown in various investigations [12][13][14], one would predict that after a time interval t two rather different situations should develop from the nucleation event assumed in figure 6. It is assumed that during crystal growth the crystal shape develops into a plate-like configuration.…”
Section: Assumptionsmentioning
confidence: 76%
“…Below h = 20°, the GB contains the segments of perfect contact of abutting grains forming the high-T c ''pathways'' crossing the boundary plane. They are separated by dislocation cores with low T c [219,[225][226][227][228][229]. One can say to a first approximation, that thereafter a continuous insulating layer of 2-3 nm will lead to a constant attenuation of the supercurrent.…”
Section: Faceting-roughening In Oxidesmentioning
confidence: 99%
“…Analysis of the kink angle indicated that CB1 (in figure 10) is at a 15 • [010] tilt to the grain boundary and CB2 (in figure 10) is at an 18 • [010] tilt to the grain boundary. Colonies with kink angles of 30 • and 18 • have been observed by other investigators [29,30]. At this time, we are not sure what causes these preferred orientations of the platelets and more work needs to be done to estimate their implications on the current transport properties of the tapes.…”
Section: Resultsmentioning
confidence: 74%